Integrative Analysis of the Metabolome and Transcriptome of a Cultivated Pepper and Its Wild Progenitor Chiltepin (Capsicum annuum L. var. glabriusculum) Revealed the Loss of Pungency During Capsicum Domestication - Zhang, Bipei; Hu, Fang; Cai, Xiaotao; Cheng, Jiaowen; Zhang, Ying; Lin, Hui; Hu, Kailin; Wu, Zhiming (Frontiers in Plant Science, 2022)
Pungency is a unique characteristic of chili peppers (Capsicum spp.) caused by capsaicinoids. The evolutionary emergence of pungency is thought to be a derived trait within the genus Capsicum. However, it is not well known how pungency has varied during Capsicum domestication and specialization. In this study, we applied a comparative metabolomics along with transcriptomics analysis to assess various changes between two peppers (a mildly pungent cultivated pepper BB3 and its hot progenitor chiltepin) at four stages of fruit development, focusing on pungency variation. A total of 558 metabolites were detected in two peppers. In comparison with chiltepin, capsaicinoid accumulation in BB3 was almost negligible at the early stage. Next, 412 DEGs associated with the capsaicinoid accumulation pathway were identified through coexpression analysis, of which 18 genes (14 TFs, 3 CBGs and 1 UGT) were deemed key regulators due to their high coefficients. Based on these data, we speculated that downregulation of these hub genes during the early fruit developmental stage leads to a loss in pungency during Capsicum domestication (from chiltepin to BB3). Of note, a putative UDP-glycosyltransferase, GT86A1, is thought to affect the stabilization of capsaicinoids. Our results lay the foundation for further research on the genetic diversity of pungency traits during Capsicum domestication and specialization.